Protection of Consumer Rights when Initiating Enforcement Proceedings under a Bank Enforcement Order - Hawrylak, Łukasz (PRAWO i WIĘŹ, 2025)
The bank enforcement order was one of the most controversial banking privileges. The repeal of this institution due to its contradiction with the Constitution did not definitively end its use. The creditors were entitled to carry out enforcement proceedings under the transitional provisions which requires balancing the principle of protection of pending interests and the protection of the debtor-consumer. This paper addresses the key issues associated with initiating enforcement proceedings against consumers and clarifies any interpretative uncertainties.